The Effect of the COVID-19 Pandemic on Healthcare Workers - Abdullah Murat Tuncer (Current Overview on Disease and Health Research Vol. 4, 2022)
The coronovirus pandemic has not only been a health problem but has also caused social problems that are impossible to end in the short term. Especially the effects are very deep on health workers. Depression, anxiety, and fear of the future are most common feelings among the people and health workers. Health system and health policy must figure out pandemic as a social problem at the same time.